Perancangan Dashboard Monitoring Stok Berbasis Web dengan Integrasi Google Spreadsheet - Setiadi, Teguh; Yasin, Verdi; Yulianto, Akmal Budi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The aim of this study is to develop a web-based application for monitoring stock that is integrated with Google Spreadsheet. The research uses the Prototype Method to develop an initial system prototype, which is then followed by Usability Testing to assess the effectiveness of the user interface and user experience. This application allows warehouse staff and technicians to monitor the availability and status of devices in real-time, thereby improving device stock management. Through iterative testing and prototyping, user feedback is incorporated into the design to enhance functionality and usability. This study demonstrates that combining these methods results in a user-focused design, improving the efficiency and usability of the application in stock management